Praktek Stimulasi Motorik Kasar Ditinjau dari Pengetahuan Ibu Mengenai Tahap Perkembangan Bayi 0-12 Bulan - Hardika, Mufida Dian (Universitas Aisyah Pringsewu, 2018)
Psychomotor development is the result of environmental stimulation beyond the individuals associated with the motion and posture. Children who get a good stimulation will grow faster optimally according to age of development. The result of observation in Krajan Posyandu (Maternal and Child Health Centre), Dolopo village, Madiun region found 60 percent mothers who do not practicing Psychomotoric stimulation yet. It is because the lack of knowledge about the steps of improvement. This study aims to determine the relationship of mother's knowledge about the stages of development with the practice of psychomotor stimulation in infants 0-12 months. This research is a quantitative research using correlational method. Data were collected using questionnaire and check list on 25 respondents. Data were analyzed using Spearman Rank statistic test with significance value p less than 0,05. The results of this study showed p value of 0.028 (p less than 0.05). The coefficient correlation between the two variables shows the number 0.439 (Positive) so there is a significant and unidirectional relationship, it shows that there is enough, significant, and the same aim of relation. It is mean that the mothers who have knowledge about developmental stage, psychomotoric stimulation practice skill to infant 0 – 12 months will increase. Finally, the researcher gives suggestions. It is supposed there is increasing activity from health officer to mothers by giving information about developmental stage and practice training of psychomotoric stimulation in infant 0 – 12 months.